Pengetahuan dan tindakan orang tua tentang pertumbuhan gigi tetap dengan terjadinya gigi crowded pada anak sekolah dasar - Imran, Herry; Wilis, Ratna; Nasri, Nasri; Niakurniawati, Niakurniawati (Poltekkes Kemenkes Aceh, 2024)
Background: Crowded teeth are a condition where the teeth are crowded together in the oral cavity because the jaw is small so it does not accommodate enough teeth. Based on the initial examination carried out by researchers at SDN Gue Gajah, 20 students consisting of class I to class IV, 18 of them had grown teeth while the other 2 had normal tooth structure and based on the results of interviews with 10 parents, 6 of them did not observe any loose teeth in children.Objective: The aim of the research is to determine the relationship between parents' knowledge and actions regarding the growth of permanent teeth and the occurrence of crowded teeth.Method: This research method is analytical, the research was carried out at SDN Gue Gajah, Darul Imarah District, Aceh Besar from 09 to 15 July 2022. The sample was 83 students, parents and mothers as respondents. Data collection was carried out by interviews and direct dental examinations of respondents.Results: The results of the study showed that crowded teeth were most dominant in mothers with poor knowledge and actions, namely 56%, with P value = 0,006 with α (0,05).Conclusion: There is a relationship between knowledge and actions of parents/mothers regarding tooth growth and the occurrence of crowded teeth in students at SDN Gue Gajah, Darul Imarah District, Aceh Besar in 2022.